Memory of departure - Gurnah, Abdulrazak (London Jonathan Cape, 2021)
The arrival of independence brings new upheavals as well as the betrayal of the promise of freedom. The new government, fearful of an exodus of its most able men, discourages young people from travelling abroad and refuses to release examination results. Deprived of a scholarship, Hassan travels to Nairobi to stay with a wealthy uncle, in the hope that he will release his mother's rightful share of the family inheritance.
Keywords: Tanzania--Fiction.